Assessing the Knowledge, Attitudes, and Practices of Saudi Arabian Nurses Regarding Healthcare-Associated Infection Prevention in Geriatric Care Settings: A Quantitative Study - Wasmi Awad Sahlan Aldhafeeri; Faiz Saud Hilal Alotaibi; Rakan Mathhar Rakan Bathiraa; Majed Saket Farhan Alanazi; Hamad Hyyan Alrwily; Salah Sayer M Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This quantitative study aimed to assess the knowledge, attitudes, and practices (KAP) of Saudi Arabian nurses regarding healthcare-associated infection (HAI) prevention in geriatric care settings. Methods: A cross-sectional survey was conducted among 500 nurses working in geriatric care facilities across Saudi Arabia. The survey questionnaire consisted of four sections: demographic information, knowledge about HAI prevention, attitudes towards HAI prevention, and practices related to HAI prevention. Descriptive statistics, independent t-tests, and one-way ANOVA were used to analyze the data. Results: The overall mean scores for knowledge, attitudes, and practices were 75.6%, 82.3%, and 79.1%, respectively. Significant differences in KAP scores were found based on nurses' age, years of experience, and level of education (p<0.05). Nurses with higher education levels and more years of experience had better KAP scores. The most significant knowledge gaps were related to the use of personal protective equipment (PPE) and the management of medical waste. Nurses demonstrated positive attitudes towards HAI prevention, but some reported barriers such as workload and lack of resources. Conclusion: While Saudi Arabian nurses have good overall KAP regarding HAI prevention in geriatric care settings, there are areas for improvement. Targeted educational interventions and strategies to address identified barriers are recommended to enhance nurses' KAP and ultimately improve patient outcomes.